Effect of zinc foliar application on grain yield of maize and its yielding compone - J. Potarzycki; W. Grzebisz (Plant, Soil and Environment, 2009)
Actual yields of maize harvested by farmers are at level much below attainable yield potential of currently cultivated varieties. Among many growth factors zinc was recognized as one of main limiting factors of maize crop growth and yielding. This hypothesis has been verified within a three-year field study, where zinc fertilizer was applied to maize plants at the 5th leaf stage. Maize crop responded significantly to zinc foliar application in two of three years of study. The optimal rate of zinc foliar spray for achieving significant grain yield response was in the range from 1.0 to 1.5 kg Zn/ha. Grain yield increase was circa 18% (mean of three years) as compared to the treatment fertilized only with NPK. Plants fertilized with 1.0 kg Zn/ha significantly increased both total N uptake and grain yield. Yield forming effect of zinc fertilizer revealed via improvement of yield structure elements. The number of kernels per plant showed the highest response (+17.8% as compared to the NPK plot) and simultaneously the highest dependence on N uptake (R2 = 0.79). For this particular zinc treatment, however, the length of cob can also be applied as a component of yield structure significantly shaping the final grain yield.